AutoCAD 2010 & AutoCAD LT 2010 bible - Finkelstein, Ellen (Bible., 2009)
A guide to AutoCAD and AutoCAD LT provides a tutorial on the basics of creating drawings, using commands, and specifying coordinates, and covers more complex 2D and 3D drawing techniques, including using layers, creating dimensions, 3D coordinates, solids, and rendering.